Evaluation of the Efficacy of the Non-Decompressive Single Stage Bilateral Craniotomy in Treatment of Traumatic Brain Injury - Akramuallah, Sajid Khan, Muhammad Zubair, Sahibzada Haseeb Ahmad, Tariq Jamal, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Traumatic brain injury is one of the major health care problem around the globe. It is heterogeneous entity. Traumatic lesions including fracture and hematomas typically require surgery. Objective: The study aimed to analyze the Non-Decompressive Single Stage Bilateral Craniotomy in the patients suffering from traumatic brain injury. Study design: This prospective and single center based study was conducted at the neuroscience department of Prime Teaching Hospital/ Peshawar Medical College for the duration of the six months from January 2022 to June 2022. Material and Methods: Out of all the patients visited the neuroscience department of our institute teaching hospital, only 40 were selected for the study after analysis of the computed tomography images. These 40 fulfilled the inclusion criteria. The ethical and review board committee of our hospital approved the study. The patients willingly signed the consent. The bilateral frontal contusectomy was most commonly used surgical procedure. While other used surgical procedures were contralateral contusion and unilateral epidural hematoma. Results: Out of all the patients admitted in the hospital there were 40 that met all the requirements of the study. There were 30 men and 10 women. Most of the cases were reported in the range of 40-59 age. Middle aged men were mostly effected by the disease. The cases were almost in equal number as far as severity of the Traumatic brain injury is concerned. There were some patients that developed ventilator acquired pneumonia and some of the participants suffered from urinary tract infection along with a case of wound infection. There were some death cases reported as well. There were some of the patients who quit medical advice because of their poor financial state. Conclusion: To deal with traumatic brain injury in an effective way, SSBC can prove to be a safe and cost effective procedure, as it has multiple advantages like single incision, single anesthesia and reduced surgical charges, the management of the patient after operation is similar to that of unilateral procedure. Stay in hospital is also reduced and opposite lesion condition can also be avoided this way. Keywords: Traumatic brain, injury, surgical treatment and unilateral procedures.